Intersectionnalité, diversité capacitaire et diversité ethnoculturelle - Véro Leduc; Sendy-Loo Emmanuel (Communication)
This article focuses on cultural equity for a very small and under-researched group, members of capacity diversity groups (Leduc et al., 2020a)—a term for the diversity of deaf or disabled people or members of neurominorities or psychominorities, (Leduc, 2022) who may also identify with different ethnocultural groups. This article provides an intersector analysis of issues faced by artists and cultural workers who are members of these diversity groups. It looks at issues of cultural belonging and representation and suggests ways of implementing greater cultural equity to make it easier for members of this group to exercise their cultural citizenship.